2020
DOI: 10.33417/tsh.662982
|View full text |Cite
|
Sign up to set email alerts
|

Palyatif Bakım Hasta Yakınları İle Nitel Bir Çalışma

Abstract: Palyatif bakım, hastalığı daha fazla tedavi edilemez olan hastaları, hastalıklarının son aşamasına kadar yaşam kalitelerinin artması ve acılarının azaltılması açısından destekleyen bir hizmettir. Giderek yaşlanan nüfus ve toplumun bireyselleşmesiyle bağlantılı olarak ailenin sorumluluklarının azaldığı dünya şartlarında palyatif bakımın ve palyatif bakım hasta ve hasta yakınlarına yönelik sosyal hizmetin rolü giderek daha fazla önem kazanmaktadır. Bu araştırmanın amacı palyatif bakımın hasta yakınları üzerindek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…It is believed that paid caregiving can create an economic burden and pose difficulties within the family. Similar findings indicating that caregivers experience economic difficulties during the caregiving process can be found in the literature [14,22,31]. These findings underscore the necessity of providing professional support to address the problems faced by caregivers, as well as the importance of institutional and home care services.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is believed that paid caregiving can create an economic burden and pose difficulties within the family. Similar findings indicating that caregivers experience economic difficulties during the caregiving process can be found in the literature [14,22,31]. These findings underscore the necessity of providing professional support to address the problems faced by caregivers, as well as the importance of institutional and home care services.…”
Section: Discussionsupporting
confidence: 85%
“…When the findings obtained in the study are evaluated, it is notable that the provision of care is primarily undertaken by females. Many studies conducted with the relatives of patients requiring care have revealed that carers are predominantly female [14,[18][19][20][21][22]. In Turkish society, females are also more typically assigned to caregiving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] In a similar study in which the loss of social roles and economic problems were emphasized, it was stated that the participants needed moral and companion support. [16] There are limited studies in the literature on the methods of coping with the problems of the relatives of patients who experience many psychological, social and economic problems. In a study conducted with the relatives of palliative care patients, it was shown that 91% of the participants tried to cope with the problems in the disease process through religious methods and 65.5% through social support.…”
Section: Discussionmentioning
confidence: 99%
“…Palyatif bakım, yaşamı tehdit edici hastalığı olan bireyin semptomlarının azaltılmasını sağlayan, hasta ve ailesinin yaşam kalitesini arttırmayı hedefleyen, multidisipliner bir bakım yaklaşımıdır (Maciver ve Ross, 2018). Palyatif bakım kliniklerinde kanser, kronik obstrüktif akciğer hastalığı, multiple skleroz gibi nörodejeneratif hastalıklar, geriatrik ve romatolojik hastalıklar, diyabet ve böbrek yetmezliği tanılı hastalar bakım almaktadır (Benli ve Sunay, 2017;Turgut ve Soylu, 2020). Palyatif bakımın temel amacı, hastanın konforunu sağlamak ve ağrı başta olmak üzere semptomları etkili biçimde yönetmektir (Okan ve ark., 2019).…”
Section: Introductionunclassified